2024
DOI: 10.4103/jos.jos_102_23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biomechanical performance of titanium and polyaryletheretherketone miniscrews at different insertion angles: A finite element analysis

I Gusti Aju Wahju Ardani,
Intan Vallentien Dwi Hariati,
Alexander Patera Nugraha
et al.

Abstract: INTRODUCTION: Only miniscrews [temporary anchoring devices, (TADs)] can provide absolute anchorage during orthodontic treatment. Titanium (Ti) is a fundamental material used in the production of miniscrews, but it has many disadvantages. Polyaryletheretherketone (PEEK) may have various benefits in the production of miniscrews. Finite element analysis (FEA) is a valid and reliable method for calculating stress, strain, and loading forces on complex structures and can be more time- and cost-efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…At 30°angulation with 2.66 CBT , the shear stress in the interface region of T2 screw was 22% higher than 0°angulation as shown in figure 5. In line with our results a study showed when the angulation increased, the stress in miniscrew also increased due to the reduction of tension in bone [32].…”
Section: Discussionsupporting
confidence: 92%
“…At 30°angulation with 2.66 CBT , the shear stress in the interface region of T2 screw was 22% higher than 0°angulation as shown in figure 5. In line with our results a study showed when the angulation increased, the stress in miniscrew also increased due to the reduction of tension in bone [32].…”
Section: Discussionsupporting
confidence: 92%